Immune reconstitution inflammatory syndrome due to Mycobacterium genavense in an HIV-infected patient: Impact of rapid species identification by rpoB sequencing on clinical management. Issue 6 (12th December 2015) - Andre, Emmanuel; Belkhir, Leila; Goeminne, Léonie; Colmant, Alexandre; Sottiaux, Jean-Yves; Yildiz, Halil; Ruelle, Jean; Delmee, Michel; Vandercam, Bernard; Defour, Jean-Philippe
Abstract : Introduction: Diagnosis of infections due to Mycobacterium tuberculosis has been recently facilitated with the worldwide implementation of rapid molecular tests. However, the diagnosis of non-TB mycobacteria (NTM) remains a major challenge for laboratories, as this group of bacteria contains over 150 different species with highly variable bacteriological properties. The development and implementation in clinical practice of techniques allowing rapid identification of NTM at the species level is, therefore, important for clinical laboratories. We report the case of an HIV-1 positive patient presenting with severe NTM infection who benefited from a novel rapid diagnostic technique, based on the direct sequencing of the rpoB gene from smear-positive clinical samples. Case Presentation: A 43-year-old HIV-1 positive woman was hospitalized for bicytopenia in the presence of an inflamed supraclavicular lymph node. The diagnosis of disseminated Mycobacterium genavense infection, which involved the bone marrow and several lymph nodes, was missed by conventional mycobacteriological techniques. Identification was obtained by performing direct sequencing of the rpoB gene. Conclusion: We describe a novel technique that allows the rapid diagnosis of NTM infections directly from biological samples. This technique is now implemented in our routine workflow for smear and culture-positive samples, after the exclusion of TB, by rapid molecular assays.